PENDAMPINGAN IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KARIER (PROMOSI, ROTASI DAN DEMOSI) UNTUK PENINGKATAN SUMBER DAYA MANUSIA BANK PUNDI INDONESIA - Ruslina Dwi Wahyuni (LPPM STAIMAS WONOGIRI, 2021)
In building the company in the future, employees who continue to develop both in competence, insight and experience are needed, so good governance is needed for career ladder. This paper is intended to examine the policies implemented at Bank Pundi in human resource development, especially in terms of implementing career paths, promotions, transfers and demotions at the main branch offices and sub-branch offices in business directories. A policy taken is of course adjusted to the needs of the organization and accommodates all existing elements based on professionalism and equal distribution of the quality of human resources so that they can place resources according to their competence